1996
DOI: 10.1002/(sici)1520-6327(1996)31:1<1::aid-arch1>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic and metabolic studies of sterol 24,25-double bond reduction inManduca sexta

Abstract: Larvae of Manduca sexta were used to obtain a cell‐free sterol 24,25‐reductase. From the midgut of fifth instar larvae fed a mixture of sitosterol and campesterol a microsome‐bound 24,25‐sterol reductase was prepared that transformed desmosterol (Km, 3 μM), lanosterol (Km, 18 μM), and cycloartenol (Km, 33 μM), to cholesterol, 24,25‐dihydrolanosterol, and cycloartanol, respectively. With desmosterol as substrate, the microsome‐bound enzyme was found to incorporate tritium into cholesterol from 4S‐tritium labell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It was also found using intact Manduca sexta, that conversion of [24- 2 H]lanosterol to [24- 2 H]dihydrolanosterol proceeds with retention of 2 H at C24 and that incubation of [4- pro - S - 3 H]NADPH paired with desmosterol leads to the incorporation of tritium into cholesterol. ( 148 ) The summation of the stereochemical experiments are illustrated in the revised mechanism of sterol C24-reduction illustrated in Figure 16 , which shows that the addition of hydrogen on the substrate 24(25)-double bond takes place in anti fashion from the re- face of C24 and the si -face of C25 and that the pro- S hydrogen is transferred from a nicotamide cofactor to the C25 cation intermediate. The only other enzymatic studies of sterol side chain reductase beyond those involving Δ 24(25) -reductases have targeted the yeast sterol 28-SR, which has been found to prefer ergosta-5,7,22,24(28)-tetraenol as the optimal substrate and to require NADPH in conversion of the 24(28)-double bond to 24β-methyl sterol.…”
Section: Sterol Enzyme Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was also found using intact Manduca sexta, that conversion of [24- 2 H]lanosterol to [24- 2 H]dihydrolanosterol proceeds with retention of 2 H at C24 and that incubation of [4- pro - S - 3 H]NADPH paired with desmosterol leads to the incorporation of tritium into cholesterol. ( 148 ) The summation of the stereochemical experiments are illustrated in the revised mechanism of sterol C24-reduction illustrated in Figure 16 , which shows that the addition of hydrogen on the substrate 24(25)-double bond takes place in anti fashion from the re- face of C24 and the si -face of C25 and that the pro- S hydrogen is transferred from a nicotamide cofactor to the C25 cation intermediate. The only other enzymatic studies of sterol side chain reductase beyond those involving Δ 24(25) -reductases have targeted the yeast sterol 28-SR, which has been found to prefer ergosta-5,7,22,24(28)-tetraenol as the optimal substrate and to require NADPH in conversion of the 24(28)-double bond to 24β-methyl sterol.…”
Section: Sterol Enzyme Actionmentioning
confidence: 99%
“…The substrate specificity of the sterol C24-reductase has been examined in two cases, in rat and insect (Manduca sexta ) microsomal preparations. , The catalytic competence for the two enzymes differ markedly in their recognition of the cholestane and lanostane frame. The apparent V max / K m for lanosterol and desmosterol are for rat 0.361 nmol/(min·mg) and 109 μM and 3 nmol/(min·mg) and 163 μM compared with the insect 3 pmol/(min·mg) and 18 μM and 1 pmol/(min·mg) and 3 μM, respectively.…”
Section: Sterol Enzyme Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…1275 Subsequent conversion of the 24 -steroid desmosterol (91) to cholesterol (33) requires a sterol 24 -reductase: studies with Manduca sexta have shown that a variety of sterols can be reduced 1276 and the microsomal enzyme has been characterised. 1277 The C-25 hydrogen is introduced stereospecifically from the si-face of the double bond. 1272 The most intensively studied area of insect steroid biosynthesis is the modification of dietary steroids to ecdysteroids, the hormones which control insect moulting behaviour.…”
Section: Biosynthesis Of Steroids In Insectsmentioning
confidence: 99%